Effects of the plant growth regulators, cobalt and molybdenum on the physiology of ‘Crimson Seedless’ grapevines - Baron, Amanda Cristina Esteves Amaro [UNESP]; Baron, Daniel; Souza, Essione Ribeiro [UNESP]; Moreira, Laíse Sousa; Ono, Elizabeth Orika [UNESP]; Rodrigues, João Domingos [UNESP] (Springer Nature, 2022)
Hormonal balance is important for plant metabolism and, consequently, berry development of grapevines (Vitis vinifera L.). Exogenous application of plant growth regulators (PGRs) combined with mineral elements, in satisfactory dosages, can promotes physiologic efficiency. We investigated the effect of foliar application of PGRs alone or combined with mineral elements on 'Crimson Seedless’ grapevines. The metabolism and development of the plants were examined. The treatments were applied via foliar spraying consisting in a PGRs mixture [cytokinin (kinetin—Kt), auxin [4-Indole-3-butyric acid (IBA)], and gibberellin (gibberellic acid—GA3)] and a cobalt (Co) and molybdenum (Mo) mixture were studied. The PGRs and nutrients combined acted as protectors against stress, presenting increases in antioxidant enzyme activities but with a low level of lipid peroxidation. We concluded that the mixture of PGR applied alone or combined with mineral elements favoured content of photosynthetic pigments in the grapevines leaves, antioxidant enzyme activity, translocation and accumulation of reserves.
Keywords: Crop plants; Plant biochemistry; Plant growth regulators; Plant nutrition; Plant physiology